2022
DOI: 10.1021/acs.jmedchem.2c00609
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Clinical Candidate CHF-6366: A Novel Super-soft Dual Pharmacology Muscarinic Antagonist and β2 Agonist (MABA) for the Inhaled Treatment of Respiratory Diseases

Abstract: The development of molecules embedding two distinct pharmacophores acting as muscarinic antagonists and β2 agonists (MABAs) promises to be an excellent opportunity to reduce formulation issues and boost efficacy through cross-talk and allosteric interactions. Herein, we report the results of our drug discovery campaign aimed at improving the therapeutic index of a previous MABA series by exploiting the super soft-drug concept. The incorporation of a metabolic liability, stable at the site of administration but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, if the linker is too long, the high flexibility would also impair the potency and selectivity. 62,[233][234][235][236][237][238][239][240][241] In fact, a major workload in many researches is to decide the optimal length of the linker. To reduce the burden workflow, rational strategies are urgently needed.…”
Section: Bridging Orthosteric and Allosteric Pharmacophores With A Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, if the linker is too long, the high flexibility would also impair the potency and selectivity. 62,[233][234][235][236][237][238][239][240][241] In fact, a major workload in many researches is to decide the optimal length of the linker. To reduce the burden workflow, rational strategies are urgently needed.…”
Section: Bridging Orthosteric and Allosteric Pharmacophores With A Pr...mentioning
confidence: 99%
“…In drug metabolism, however, dynamics linkers mean easier degradation of the linkers. As an example, Carzaniga et al 236 added an ester group into the alkyl linker of a dualsteric MR agonist. It was found that such a modification has a small effect on the overall potency but contributes greatly to metabolism.…”
Section: Bridging Orthosteric and Allosteric Pharmacophores With A Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they both appear to be discontinued and the examination of published preclinical and clinical data supports the speculation that the pharmacodynamic profile of the two pharmacological components (M 3 or β 2 ) could be divergent, with a predominance of one activity over the other, hampering the adjustment of doses when needed. 16 We were therefore encouraged to embark upon a drug discovery campaign aimed at developing an inhaled MABA that led first to the clinical candidate CHF-6366, whose discovery has been already described in a previous work, 15 and lately to the identification of a novel class of heterobifunctional diphenyl hydroxyacetic esters as inhaled MABA for respiratory diseases, the object of this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Considering our interest in SKRs on GPCR ligands, 29 and, in particular, in M3 antagonists as single 30,31 or dual targeting agents, 32,33 we selected the M3 receptor as a reference system, focusing our attention on a set of tiotropium analogues for which experimental RTs have been recently reported by Tautermann and colleagues (Figure 2), 34 and X-ray structures are currently available. Moderate modifications in the structure of tiotropium, including the removal of thiophene (1) or of an α-hydroxyl substituent (9), lead to a significant reduction in the experimental RT (over different orders of magnitude), suggesting that this set of compounds is suitable for the setup and test of computational protocols for SKR rationalization.…”
Section: ■ Introductionmentioning
confidence: 99%